Analysis of Factors Determining Competence in Vocational Teacher Candidates: A SEM Approach - Suhartanta Suhartanta; Kurniawan Sigit Wahyudi; Amir Fatah (Journal of Vocational Education Studies, 2026)
Efforts to improve the competence of prospective vocational teachers require educational management that effectively integrates institutional factors and learning quality. This study aims to analyze the determinant factors influencing the competency formation of prospective vocational teacher candidates in higher education. A quantitative survey design was employed involving 278 respondents, consisting of 73 lecturers and 205 alumni selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test a structural model involving six latent variables, 58 indicators, and 32 hypotheses. The results show that graduate competence can be explained by the proposed model with an R² value of 71.90%. Social adaptation skills, character and exemplary behavior, motivation, and goal achievement emerged as dominant indicators of competency formation, while understanding of current technology showed the lowest contribution. The findings also indicate that learning quality plays a central mediating role in transforming institutional factors, including managerial leadership, academic culture, academic atmosphere, and lecturer competence, into graduate competence. This study contributes to the development of an integrated model of vocational teacher competency formation and provides practical implications for Teacher Education Institution leaders in strengthening leadership practices, lecturer development, and learning quality improvement.